Studi Komparasi Kompetensi Guru Matematika SD di Indonesia dan Inggris - Febriarsita Eka Sasmita; M. Amin; Masfufah Masfufah (Departement of Mathematics Education, 2024)
Teachers are a very important element and cannot be ignored just like that in the teaching and learning process, because teachers can determine the success or failure of a teaching and learning process. All teachers in any field including Mathematics need to have competencies to maximize teaching and learning activities. These standards and competencies are believed to be encouraged by each country to each teacher, considering how the role of teachers can implicitly impact the progress of each country. Developed countries that are known to have good quality in the field of Education Based on this, researchers wrote a comparative study related to the competence of mathematics teachers, especially elementary schools in Indonesia and in the UK. Researchers use the method of literature study. Both countries have many good competencies that need to be mastered. The form of quality assurance from the UK can be an example for the Indonesian state to prepare students in Indonesia to face the 21st century.